Diagnosis of oral disorders in patients with chronic kidney disease - Irina K. Lutskaya (LLC "MEDIAFORMAT", 2021)
Chronic kidney disease results in severe disruptions to metabolic pathways, which contributes to tissue and organ damage, including damage to oral mucosa. A long-term condition limits the patient's activity, which results in poor oral hygiene. Accumulation of dental plaque causes inflammation of the gums and follows the development of lesions in various areas of mucous membrane. Raches become long-lasting (chronic) and bother the patient. Bleeding gums immediately during hemodialysis is a clear manifestation of coagulation disorders. The research made it possible to develop guidelines on dental care in patients with CKD.